(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2025)
The article explores the complex nature of researcher positionality in an observational study centered on collaborative learning (CL) within an English as a Foreign Language (EFL) classroom. The classroom was the main research setting but the article primarily emphasizes on the researcher’s shifting positionality/roles between being an active-participant (a facilitator and advanced L2 learner) and a passive observer and the reflexive approach to positionality. The researcher gained access to the classroom through the institute at the administrative level and the English teacher who facilitated entry into the classroom and moderately influenced the expectations associated with the researcher’s role. As a novice researcher, I experienced shifts in identity. My active participation in both virtual and physical classes influenced my positionality as an insider. Given my shared linguistic and learning background with the students, some perceived me as an insider, and semi-insider. However, at times, I felt like a complete outsider; my role as a passive observer and the resistance from some students positioned me as one. These changes in positionality influenced the nature of interactions and the research outcomes. These shifts also highlight the fluid aspect of positionality. Drawing on Pechurina’s (2014) insights from her ethnographic study of Russian migrants, this article illustrates that positionality is dynamic and constantly negotiated within different relationships. These experiences highlight the significance of reflexivity as both methodological and ethical practice, demonstrating how the researcher’s identity shapes what is observed, interpreted, and presented in qualitative educational research.